The Effectiveness of Acceptance and Commitment Therapy (ACT) on Enhancing Academic Motivation and Reducing Academic Underachievement in Students with Working Memory Disorder - Iranshahri, Bahram; Soghara Karbalaei Herofteh, Fatemeh; Sanagouye Moharer , Gholamreza (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The objective of this study was to investigate the effectiveness of Acceptance and Commitment Therapy (ACT) in enhancing academic motivation and reducing academic underachievement among high school students with working memory disorders. Methods and Materials: This research utilized a quasi-experimental pretest-posttest design with a control group and a three-month follow-up. The statistical population included all male students in the second grade of secondary school in Iranshahr who had diagnosed working memory impairments. Through purposive sampling, 40 students were selected and randomly assigned into two equal groups (20 experimental, 20 control). The experimental group participated in eight structured ACT sessions, while the control group received no intervention. Data collection tools included the Harter Academic Motivation Scale and the Pham and Taylor Academic Performance Questionnaire, both validated and reliable for the target population. Data were analyzed using repeated measures ANOVA and Bonferroni post hoc tests via SPSS. Findings: The results indicated that the ACT intervention had a significant effect on increasing academic motivation (F(1,38) = 54.455, p < .001, η² = .589) and reducing academic underachievement (F(1,38) = 664.471, p < .001, η² = .946). Repeated measures ANOVA also showed significant effects of time and time*group interaction on both variables (p < .001). Bonferroni tests confirmed that differences between pretest and posttest, as well as pretest and follow-up, were significant (p < .001), while posttest to follow-up differences were not significant, indicating sustained effects. Conclusion: The sustained improvements observed suggest that ACT fosters lasting changes through psychological flexibility and value-based action.